2019
DOI: 10.1039/c9mo00029a
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of the protective effect of rubusoside on palmitic acid-induced lipotoxicity in INS-1 cells using UPLC-Q/TOF MS

Abstract: Diabetes is one of the most severe chronic diseases worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similar to previously described, KEGG analysis was mainly enriched in metabolic pathways that are related to IR or diabetes, including metabolism of xenobiotics by cytochrome P450 ( 47 ), steroid hormone biosynthesis ( 48 ), retinol metabolism ( 49 ), ascorbate and aldarate metabolism ( 50 ), pentose and glucuronate interconversions ( 51 ), starch and sucrose metabolism. Several canonical pathways outstood among the statistics, including PI3K-Akt pathway, MAPK pathways and Rap1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previously described, KEGG analysis was mainly enriched in metabolic pathways that are related to IR or diabetes, including metabolism of xenobiotics by cytochrome P450 ( 47 ), steroid hormone biosynthesis ( 48 ), retinol metabolism ( 49 ), ascorbate and aldarate metabolism ( 50 ), pentose and glucuronate interconversions ( 51 ), starch and sucrose metabolism. Several canonical pathways outstood among the statistics, including PI3K-Akt pathway, MAPK pathways and Rap1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics is an important aspect of systems biology. Currently, commonly used analytic methods include partial least squares discriminant analysis (PLS‐DA), principal component analysis (PCA), and orthogonal partial least squares discriminant analysis (OPLS‐DA) (Fond et al, 2013; Zheng et al, 2019). Through the analysis of serum, urine, feces and other biological samples, we could discuss the changes of small‐molecule metabolites in various metabolic pathways and the effect of natural active ingredients of drugs on disease treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low calories, safety and high sweetness of RS, it is used to replace sucrose and synthetic sweeteners. Recent research has demonstrated that RSs exhibit significant bioactivities, such as antiallergic (Wang et al, 2020), anti-carcinogenic (Chu et al, 2016) and anti-lipotoxic activities (Zheng et al, 2019). RSs can also achieve the solubilization of drugs (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%